Oligo-Carrageenan Kappa-Induced Reducing Redox Status and Activation of Trr/Trx System Increase the Level of Indole-3-Acetic Acid, Gibberellin a 3 and Trans-Zeatin in Eucalyptus Globulus Trees - Zuniga-Navarro, G; Moenne-Munoz, A; Contreras-Arredondo, R; Gonzalez-Figueroa, A (Multidisciplinary Digital Publishing Institute (MDPI), 2014)
Eucalyptus globulus trees treated with oligo-carrageenan (OC) kappa showed an increase in NADPH, ascorbate and glutathione levels and activation of the thioredoxin reductase (TRR)/thioredoxin (TRX) system which enhance photosynthesis, basal metabolism and growth. In order to analyze whether the reducing redox status and the activation of thioredoxin reductase (TRR)/thioredoxin (TRX) increased the level of growth-promoting hormones, trees were treated with water (control), with OC kappa, or with inhibitors of ascorbate synthesis, lycorine, glutathione synthesis, buthionine sulfoximine (BSO), NADPH synthesis, CHS-828, and thioredoxin reductase activity, auranofine, and with OC kappa, and cultivated for four additional months. Eucalyptus trees treated with OC kappa showed an increase in the levels of the auxin indole 3-acetic acid (IAA), gibberellin A3 (GA3) and the cytokinin trans-zeatin (t-Z) as well as a decrease in the level of the brassinosteroid epi-brassinolide (EB). In addition, treatment with lycorine, BSO, CHS-828 and auranofine inhibited the increase in IAA, GA3 and t-Z as well as the decrease in EB levels. Thus, the reducing redox status and the activation of TRR/TRX system induced by OC kappa increased the levels of IAA, GA3 and t-Z levels determining, at least in part, the stimulation of growth in Eucalyptus trees. © 2014 by the authors.